Rural water projects in Bolivia: Experience from Mi Agua Program - Valverde, Osvaldo; Rojas-Ortuste, Franz; Cordero, Dilberth (2020)
General objective: Implement a comprehensive and multisector model (Ministry of Environment and Water, Ministry of Health, Ministry of Education, Cooperation Agencies and CAF) for effective promotion on water, hygiene, nutrition and child development practices) to reducing chronic malnutrition prevalence in children under the age of five.